Identifikasi Tingkat Pemahaman Materi Gerak Lurus Pada Siswa Kelas X MIPA SMAN 1 Muaro Jambi - Wicaksono, Langgeng Yoga; Ramadhanti, Auliya; Simamora, Nadia Natalia (Cahaya Ilmu Cendekia Publisher, 2022)
Purpose of the study: This study aims to identify the level of understanding of draft student class X MIPA against Theory motion straight. Methodology: A Study was conducted on 13-19 October 2020 at SMA Negeri 1 Muaro Jambi. A study was conducted with instruments in the form of a questionnaire containing questions about the Theory of motion straight. Data collection techniques are carried out with the method student fill in the questionnaire given in the form of questions about Theory motion straight via the google form link. Main Findings: From the research conducted generated data, 42% of the sample had a level lack of understanding of the Theory of motion straight, 36% of the sample had a level enough understanding of the material, 12% of the sample had level good understanding, 8% sample has level very poor understanding to material and only 2% of samples that have a level very good understanding to Theory motion straight taught. So can be concluded that participant students at SMAN 1 Muaro Jambi lack understanding of the Theory of motion straight that is taught and learned. Novelty/Originality of this study: Understanding is the ability of somebody to understand or understand something after something that is known or remembered, including the ability to catch meaning from the meaning of the material studied, which is stated with decipher contents tree from something reading, or change the data presented in form certain to other forms.